Challenging Hegemony through a Quranic and Gramscian Perspective in the Tafsir of Sayyid Qutb on Social Class - Ramadhan, Zulfi Muhammad; Iqbal, Asep Munawar; Mutmainnah, Rahayu; Nurdin, Yanyan (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
Sayyid Qutb’s tafsir, particularly Fi Zilal al-Qur’an, presents a framework of social ethics grounded in tawhid, positioning it as both a spiritual principle and a basis for confronting structural oppression. His analysis of the Qur’anic concepts of mala’ (elite classes) and mustad’afin (the oppressed) offers a critical entry point for understanding class struggle within Islamic thought. This study aims to contextualize Qutb’s discourse on mala’ and mustad’afin by engaging Antonio Gramsci’s theory of hegemony, with the goal of constructing a Qur’an-based model of counter-hegemony that responds to contemporary social inequality. Using a qualitative textual approach, the study analyzes key Makkiyah verses interpreted by Qutb through the al-adabi al-ijtima’i method. These interpretations are then integrated with Gramsci’s concepts of ideological control, organic intellectuals, and war of position to assess their relevance in modern social contexts. The findings show that Qutb’s tafsir aligns with Gramscian critical theory in viewing structural inequality as maintained through cultural and ideological mechanisms. The mustad’afin are positioned as morally empowered actors, capable of resisting hegemony through ethical leadership, ideological education, and faith-based collective action. This study affirms that the integration of Qutb’s tafsir with Gramscian analysis offers a socially engaged Qur’anic hermeneutic. It demonstrates the potential of Islamic thought to address systemic injustice through a praxis-oriented framework grounded in divine justice, ethical redistribution, and spiritual resistance.